The Influence of AI Technology, Principal's Leadership, and Motivation on Teacher Performance - Hartini Haritani; Hary Murcahyanto; Abd. Syakur (At- Ta'lim : Jurnal Pendidikan, 2026)
This study aims to analyze the simultaneous influence of AI Technology, Principal Leadership, and Motivation on Teacher Performance in East Lombok. Using multiple linear regression, data were collected via a questionnaire distributed to 9 selected teachers via purposive sampling. The analysis showed that AI Technology had a significant positive influence on Teacher Performance, with a regression coefficient of 0.588 and a p-value of 0.035, while Principal Leadership and Motivation had negative effects, with regression coefficients of -0.165 and -0.003, respectively, though the effect of motivation was very small. This regression model explains 84.2% of the variation in Teacher Performance, with AI Technology having the greatest influence. Simultaneous tests showed that the overall regression model was significant (p-value for F = 0.035), indicating that all three independent variables contributed to improving teacher performance. This research emphasizes the importance of applying AI Technology in education, as well as the need to improve school principals' leadership styles and deepen understanding of teacher motivation.